1971
DOI: 10.1071/ea9710473
|View full text |Cite
|
Sign up to set email alerts
|

Studies in flock mating of sheep. 4. The relation of libido tests to subsequent service activity of young rams

Abstract: Seventy-five Merino rams, l 1/2 years old, were tested for libido in pens and were later observed while mating in flocks. The total number of services performed in three pen libido tests was the parameter most highly correlated with service frequency during flock mating. For the 58 rams that mounted ewes in the libido tests, the total number of services in the three tests was highly correlated with the number of services performed during the first three hours in flocks of 40 ewes containing only one ram (r56 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

1976
1976
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 0 publications
0
17
2
Order By: Relevance
“…The serving capacity test was first developed by Mattner and colleagues in Australia (Mattner et al, 1971). These scientists defined serving capacity as "the number of matings with estrous ewes a ram achieves in a specific time period when confined to a pen of limited size."…”
Section: How To Study Sexual Behavior In Sheepmentioning
confidence: 99%
“…The serving capacity test was first developed by Mattner and colleagues in Australia (Mattner et al, 1971). These scientists defined serving capacity as "the number of matings with estrous ewes a ram achieves in a specific time period when confined to a pen of limited size."…”
Section: How To Study Sexual Behavior In Sheepmentioning
confidence: 99%
“…Australian work with Merinos has shown that two-tooth rams mate with fewer ewes and sometimes are not as fertile as older rams (Lightfoot & Smith 1968;Croker 1970;Croker & Lindsay 1972;Mattner et al 1971Mattner et al , 1973. Two ram age groups joined with different numbers of ewes per ram were compared in two experiments to provide information on the Romney breed.…”
Section: Introductionmentioning
confidence: 99%
“…Pen libido tests (Mattner et al 1971) were conciucted with all rams in Experiments 2 and 3 a few days before joining and 17, 34, 51, and 72 days after the start of mating. Each test consisted d 20 min continuous observation of a single ram with five oestrous ewes in a small pen, all mounts and services being recorded.…”
Section: Measurement Of Libidomentioning
confidence: 99%